A Critical Plot Twist: Changing Characters and Foreshadowing the Future of Organizational Storytelling. (11th April 2019) - Beigi, Mina; Callahan, Jamie; Michaelson, Christopher
Abstract: This review explores the evolution of scholarly research about organizational storytelling over the past 40 years in a sample of 165 papers published between 1975 and 2015. The authors contend that organizational storytelling has established a conventional foothold beside the dominant, scientific narrative of organization studies. Meanwhile, the voice of critical storytelling in organizations has emerged, confirming (and extending) five organizational storytelling themes identified by Rhodes and Brown: sensemaking (and subverting); communicating (and manipulating); change, learning (and challenge); power (and dissent); and identity and identification (and alienation). This review reveals the growing influence of critical management studies, emphasizing the role stories play in disrupting conventional narratives, enriching understanding of present and future storytelling in organizations, and of organizations in general.